First 12 Months of Life for Infants in New York City, New York, With Possible Congenital Zika Virus Exposure. (24th May 2019) - Lee, Ellen H; Cooper, Hannah; Iwamoto, Martha; Lash, Maura; Conners, Erin E; Bloch, Danielle; Clark, Sandhya; Hrusa, Gili; Kubinson, Hannah; Paladini, Marc; McGibbon, Emily; Rakeman, Jennifer L; et al.
Abstract: Background: Our goal was to characterize the epidemiology and clinical significance of congenital Zika virus (ZIKV) exposure by prospectively following a cohort of infants with possible congenital exposure through their first year of life. Methods: We included infants born in New York City between 2016 and 2017 who had or were born to a woman who had laboratory evidence of ZIKV infection during pregnancy. We conducted provider/patient interviews and reviewed medical records to collect information about the pregnant women and, for infants, clinical and neurodevelopmental status at birth and 2, 6, and 12 months of age. Results: Of the 404 infants who met inclusion criteria, most (385 [95.3%]) appeared well, whereas 19 (4.7%) had a possible ZIKV-associated birth defect. Seven had congenital ZIKV syndrome, and 12 were microcephalic without other abnormalities. Although infants with congenital ZIKV syndrome manifested clinical and neurodevelopmental sequelae during their first year of life, all 12 infants with isolated microcephaly were normocephalic and appeared well by 2 months of age. Laboratory evidence of ZIKV was detected for 22 of the infants, including 7 (31.8%) with a birth defect. Among 148 infants without a birth defect and negative/no laboratory results on ZIKV testing, and for whom information was available at 1 year, 4 presented with a developmental delay. Conclusions: Among infants with possible congenital ZIKV exposure, a small proportion had possible ZIKV-associated findings at birth or at follow-up, or laboratory evidence of ZIKV. Identifying and monitoring infants with possible ZIKV exposure requires extensive efforts by providers and public health departments. Longitudinal studies using standardized clinical and developmental assessments are needed for infants after possible congenital ZIKV exposure. Abstract : Infants with congenital Zika syndrome a had poor outcome within the first 12 months of life. Among those who were potentially exposed, including those with isolated microcephaly and laboratory evidence of infection but no birth defects, adverse outcomes were reported infrequently.